Pengaruh Partisipasi Publik Terhadap Kualitas Produk Hukum Nasional - Nur Afikah Paradina; Aksan Akbar, Muhamad; Syamsul Rijal (JURNAL USM LAW REVIEW, 2026)
This study aims to analyze the causal relationship between the quality of public participation in the legislative process and the quality of national legal products, as well as to examine the juridical implications of regulations enacted without meaningful public involvement. Although Law Number 12 of 2011, as amended by Law Number 13 of 2022, guarantees public participation rights, legislative practices in Indonesia remain largely formalistic, resulting in limited substantive accommodation of public aspirations. This research employs a normative-juridical method, incorporating statutory, conceptual, and case-study approaches, and analyzes primary and secondary legal materials using qualitative and descriptive techniques. The findings suggest that public participation is a significant determinant of legislative quality, influencing social legitimacy, normative responsiveness, and regulatory effectiveness. Conversely, limited participation leads to low compliance, increased social resistance, and a higher frequency of constitutional review. The novelty of this study lies in conceptualizing public participation as a causal variable that determines legal quality through measurable indicators of legitimacy, substantive relevance, and sociological enforceability rather than merely an administrative procedural requirement. Therefore, this study recommends institutionalizing meaningful participation through transparency, structured public consultations, digital participation platforms, and mandatory follow-up mechanisms to ensure democratic, accountable, and sustainable legal products. Penelitian ini bertujuan untuk menganalisis hubungan kausal antara kualitas partisipasi publik dalam pembentukan peraturan perundang-undangan dan mutu produk hukum nasional, serta mengkaji implikasi yuridis pembentukan regulasi tanpa pelibatan masyarakat secara bermakna. Meskipun Undang-Undang Nomor 12 Tahun 2011 jo. Undang-Undang Nomor 13 Tahun 2022 telah menjamin hak partisipasi publik, praktik legislasi di Indonesia masih menunjukkan kecenderungan formalistik sehingga aspirasi masyarakat belum terakomodasi secara substantif. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan, konseptual, dan studi kasus, melalui analisis bahan hukum primer dan sekunder secara deskriptif-kualitatif. Hasil penelitian menunjukkan bahwa partisipasi publik merupakan determinan substantif kualitas legislasi yang memengaruhi legitimasi sosial, responsivitas norma, dan efektivitas implementasi hukum. Sebaliknya, minimnya partisipasi berimplikasi pada rendahnya kepatuhan, meningkatnya resistensi sosial, serta tingginya pengujian konstitusional. Kebaruan penelitian ini terletak pada perumusan partisipasi publik sebagai variabel kausal penentu kualitas produk hukum dengan indikator legitimasi, relevansi substansi, dan keberlakuan sosiologis, bukan sekadar kewajiban prosedural administratif. Oleh karena itu, direkomendasikan penguatan mekanisme meaningful participation melalui keterbukaan informasi, uji publik terstruktur, digitalisasi kanal partisipasi, dan kewajiban tindak lanjut atas masukan masyarakat guna mewujudkan produk hukum yang demokratis, akuntabel, dan berkelanjutan.